Variations on a theme: two structural motifs create species-specific pheromone channels for multiple species of South American cerambycid beetles - Silva, Weliton D. (2020)
We describe the identification, synthesis, and field-testing of aggregation-sex pheromones, or likely pheromone candidates, of seven species of South American cerambycid beetles in the subfamily Cerambycinae, of the tribes Eburiini and Neoibidionini. Analyses of extracts of volatiles released by adult males revealed that Eburodacrys dubitata White produce 11-methyltridecanal, whereas the males of Eburodacrys assimilis Gounelle, Eburodacrys flexuosa Gounelle, and Eburodacrys lenkoi Napp and Martins produce blends of this compound, along with its analog 10-methyldodecanal. In contrast, males of Compsibidion graphicum (Thomson) and Compsibidion sommeri (Thomson) produce blends of 10-methyldodecanal and its corresponding alcohol 10-methyldodecanol. The results from field bioassays with synthetic compounds showed that each species was specifically attracted to traps containing their reconstructed pheromone blend. However, E. assimilis was not trapped, possibly due to inhibition by non-natural enantiomers in the racemic test compounds. During the trials for the Compsibidion species, adults of another cerambycid species, Tetraopidion mucoriferum (Thomson), were captured in significant numbers in traps baited with 10-methyldodecanol, suggesting that this compound is a pheromone component for this species. This study demonstrates another case of conservation of pheromone structures within South American cerambycid species. It also highlights how blends of closely related structures, differing only in chain length or functional group, make the evolution of species-specific pheromone channels possible.